Re3 Glass: A new generation of Recycable, Reducible and Reusable cast glass components for structural and architectural applications - Telesilla Bristogianni; Faidra Oikonomopoulou; Lida Barou; Fred Veer; Rob Nijsse; Erwin Jacobs; Giulia Frigo (Spool, 2018)
A spectacular glass brick system - developed to make the historic storefront of the Crystal Houses (Chanel store) in Amsterdam transparent - illustrates the great potential of cast glass blocks in structures. But it also reveals the need to make such constructions more sustainable. This project shows a novel, strong, circular and aesthetically pleasing building material from discarded glass, providing a solution for the problem of glass waste. Initially, different interlocking mechanisms and types of glass waste were explored. Then, physical prototypes were cast to experimentally evaluate their structural performance. The displayed glass bricks prove that glass is not only a 2D, transparent material. Instead, it can be a 3D component of unlimited shapes, colours, textures and opacity.